2021
DOI: 10.1155/2021/8853649
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphous Adenocarcinoma: A Rare Case Report with Unique Radiographic Appearance on CBCT

Abstract: Background. Polymorphous low-grade adenocarcinoma (PLGA) is a slow growing malignant tumor of minor salivary glands and is generally of indolent nature. However, according to the most recent WHO Classification of Salivary Gland Tumors (2017), the cancer is classified as Polymorphous AdenoCarcinoma (PAC). PAC presents as a less aggressive tumor, though it could on rare occasions demonstrate distant metastasis. Case Presentation. A 47-year-old man who was referred by a private practitioner for a CBCT scan in ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In the process of differentiating between various types of PAC, genetic rearrangements can play a significant role. It is found that more than 70% of the PAC cases exhibit mutations in PRKD1, and it is evident that PRKD1 variations are characteristic of this entity [ 48 ]. An example of a single-nucleotide mutation that affects a highly conserved amino acid in the kinase's catalytic loop is E710D.…”
Section: Reviewmentioning
confidence: 99%
“…In the process of differentiating between various types of PAC, genetic rearrangements can play a significant role. It is found that more than 70% of the PAC cases exhibit mutations in PRKD1, and it is evident that PRKD1 variations are characteristic of this entity [ 48 ]. An example of a single-nucleotide mutation that affects a highly conserved amino acid in the kinase's catalytic loop is E710D.…”
Section: Reviewmentioning
confidence: 99%